Pengembangan Model Laboratorium Tumbuh Kembang Anak “Audhi Day care” di UAI - Nurfadilah Nurfadilah; Nila Fitria; Rohita Rohita (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
Day care is an ECD service that assists working parents in providing health, care, protection, and education for children. The PG PAUD study program plans to develop "AUDHI Day care" at UAI as a child development laboratory that supports the development of integrated programs in urban areas. A quantitative survey was conducted to analyze the development of service and infrastructure needs. The results showed the prioritization of: 1) health and nutrition services (nutritious food, health checks, health facility referrals); 2) psychosocial and educational services (teacher-child ratios, child psychologists, teachers with S1 PAUD degrees); 3) infrastructure facilities (waiting rooms, toilets, outdoor play areas, observation rooms); 4) protection and security services (CCTV monitoring via cell phones, special security guards). Keywords - Child development laboratorium , Day care, HI ECD.